Intellectual property and developing countries: freedom to operate in agricultural biotechnology - Pardey, Philip G.; Wright, Brian D.; Nottenburg, Carol; Binenbaum, Eran; Zambrano, Patricia (International Food Policy Research Institute, 2003)
In agricultural biotechnology, the key technologies protected as intellectual property are highly concentrated in the hands of a small number of large, multinational corporations based in North America and Western Europe (“the North”). Although many developing countries (“the South”) lack the capacity to adopt these technologies, a system of international and national agricultural research centers has used them to make genetic improvements benefiting the vast majority of poor consumers. Concern is arising in the worldwide agricultural research community that the very intellectual property rights (IPRs) that have been associated with the surge of private research in biotechnology now threaten to block access to new developments to public and nonprofit researchers.